2006
DOI: 10.1086/505513
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Dietary Cetoleic Acid (22:1n‐11) in Mink (Mustela vison) and Gray Seals (Halichoerus grypus) Studied Using Radiolabeled Fatty Acids

Abstract: Cetoleic acid (22:1n-11) is a good indicator of diet in marine predators and has proven to be an important fatty acid (FA) when using adipose tissue FA composition to study diet in marine mammals and seabirds. Feeding studies have shown that 22:1 isomers are predictably underrepresented in adipose tissue relative to diet, implying that metabolism within the predator strongly influences the relationship between the level of these FAs in diet and adipose tissue. Fully understanding such metabolic processes for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The isomers of 22:1 were under-represented in the blubber of adults (present study, N3, 1.62±0.05%) and from the blubber of lactating females (1.77%) (Wheatley et al, 2008), indicating this MUFA may be conserved in juvenile muscle. Cooper et al reported similar findings in the gray seal (Halichoerus grypus) and suggested that the discrepancy between diet and blubber is a reflection of 22:1 efficient peroxisomal chain-shortening systems (22:1 to MUFAs) and de novo synthesis (22:1 to SFAs) (Cooper et al, 2006). While pups had significantly lower IMTG 22:1 values, these values correspond with published milk 22:1 values (Wheatley et al, 2008).…”
Section: Lipids In Muscle As Energy Reserves In Juvenilesmentioning
confidence: 56%
“…The isomers of 22:1 were under-represented in the blubber of adults (present study, N3, 1.62±0.05%) and from the blubber of lactating females (1.77%) (Wheatley et al, 2008), indicating this MUFA may be conserved in juvenile muscle. Cooper et al reported similar findings in the gray seal (Halichoerus grypus) and suggested that the discrepancy between diet and blubber is a reflection of 22:1 efficient peroxisomal chain-shortening systems (22:1 to MUFAs) and de novo synthesis (22:1 to SFAs) (Cooper et al, 2006). While pups had significantly lower IMTG 22:1 values, these values correspond with published milk 22:1 values (Wheatley et al, 2008).…”
Section: Lipids In Muscle As Energy Reserves In Juvenilesmentioning
confidence: 56%
“…Calibrations from juvenile harbour seals were more reliable than CCs from grey seal pups, irrespective of the FA subset employed. Further testing with calibrations generated from alternate prey and under different intrinsic conditions, as well as estimating CCs via radiolabelled FA (Cooper et al 2006), should continue. Using the newly developed Reduced FA subset provided diet estimates with the fewest false positives overall and using different FA subsets affected reported diet composition.…”
Section: Discussionmentioning
confidence: 99%
“…A more important process however, especially in mammals, may be peroxisomal chain-shortening of some long-chain monounsaturated FA. Thus, some ingested 20:1 and especially 22:1 isomers are likely shortened primarily to their 18-carbon isomers (Norseth and Christophersen 1978 ;Osmundsen et al 1979 ;Cooper et al 2005Cooper et al , 2006, r esulting in somewhat reduced and increased deposition of these FA relative to diet, respectively.…”
Section: Digestion Modification and Deposition Of Dietary Lipids Anmentioning
confidence: 99%
“…Whether this could ever be realized remains to be established, but almost certainly could not be accomplished using FA and QFASA alone. Additional tools for better understanding trophic transfer of FA in general and the performance of QFASA in particular could make use of advanced and targeted techniques, such as using radio or stable isotope-labeled FA to trace pathways from diet to deposition (Budge et al 2004 ;Cooper et al 2006) . These types of methods should provide even better insight at all trophic levels but are fairly cost-intensive.…”
Section: Summary Conclusion and The Futurementioning
confidence: 99%